PENGARUH MODEL PEMBELAJARAN KOOPERATIF TGT BERBANTUAN PERMAINAN LUDO TERHADAP HASIL BELAJAR DI SMK MUHAMMADIYAH 2 PEKANBARU - Uhti Wahidah; Suarman Suarman; Sri Kartikowati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This research aims to determine the effect of the Teams Games Tournament (TGT) model assisted by ludo game on learning achievement. This research was implemented at SMK Muhammadiyah 2th Pekanbaru. This study is Pre-Experimental Design by using One-Group Pretest-Posttest Design. The population is all of students of 11th grade AK 1 withtotal number of students are 32, all taken as sample. Then the data was analyzed used N-G and paired t Test. The average of N-Gain achievement are known to be in the "Medium" category and there are only 12 students who still get the "Low". While for the achievement of the paired t-test (group statistics) the pretest average was 76.19 with the standard deviation of 9.297 and the posttest of 88.44 with the standard deviation of 8.370. The correlation value between the TGT cooperative learning model assisted by ludo game on learning achievement that was a weak correlation and sig. 0,829. with a significant 0,005. Then the paired t test(Paired Samples Test) known sig. (2-tailed), obtained paired t test value of 0,000. It means that there were differences in learning achievement between pretest ang posttest. Because 0,000 < 0,05 (95% trusted). The average difference at pretest and posttest was 12,250. T is the value of t count, which was equal to 5.439, compared with t table in DF 30, it means the hypothesis was accepted and there were differences in learning achievement of pretest and posttest. Therefor it can be concluded that the TGT cooperative learning model assisted by the ludo game effect on learning achievement. Thus, the TGT Cooperative learning modelassisted by ludo game can be used as a learning model to be able to increase student learning achievement.Key Words: Teams Games Tournament Model, Learning Achievement